2015
DOI: 10.3892/mmr.2015.3322
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits autophagy and apoptosis in hypoxia/reoxygenation-induced myocytes

Abstract: Abstract. Primary percutaneous coronary intervention, or thombolytic therapy, provides effective myocardial blood reconstruction in patients with acute myocardial infarction to reduce acute myocardial ischemic injury. However, reperfusion can itself induce cardiomyocyte death, termed myocardial reperfusion injury (I/R). Hypoxia/reoxygenation (H/R) induces apoptosis and excessive autophagy among cardiomyocytes, leading to cell death. The present study investigated the effect of curcumin, a natural extract from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…Autophagy is anti‐apoptotic and contributes to cellular recovery during brief myocardial ischaemia, but the subsequent reperfusion could cause excessive autophagy, which is considered cytotoxic and termed as class II programmed or autophagic cell death 6, 7, 8, 26. Our previous studies showed that inhibiting excessive autophagy could significantly decrease the infarct size and improve cardiac function after I/R‐induced myocardial injury 27, 28. A similar result was observed in vitro in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Autophagy is anti‐apoptotic and contributes to cellular recovery during brief myocardial ischaemia, but the subsequent reperfusion could cause excessive autophagy, which is considered cytotoxic and termed as class II programmed or autophagic cell death 6, 7, 8, 26. Our previous studies showed that inhibiting excessive autophagy could significantly decrease the infarct size and improve cardiac function after I/R‐induced myocardial injury 27, 28. A similar result was observed in vitro in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Other molecules such as cloxyquin (a mitochondrial uncoupler and autophagy activator) and the AMPK activator PT1 also display cardioprotective effects during IR by inducing autophagy flux in both in vivo and ex vivo experiments [48,49]. On the other hand, it has not been determined yet whether the cardioprotective effect of curcumin is due to an increase or decrease in cardiomyocyte autophagy, but the currently available evidence suggests that the effects observed might be related to this process [50,51]. In line with a protective role of autophagy, tibetan patients showed an increased cardiac basal autophagy (LC3II, LAMP2, and Bnip3) as a consequence of living at high altitude and thus being exposed to chronic hypoxia [52].…”
Section: Autophagy In Cardiac Diseasesmentioning
confidence: 95%
“…However, the excessive activation of autophagy degrades some important cell structures, which eventually leads to cell death [29]. Our previous experiments demonstrated that autophagy adversely affects myocardial cells during the H/R period [3, 4] and that inhibition of excessive autophagy increases the viability of myocytes. These results indicated that autophagy regulation is an effective strategy for treating H/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…During the reperfusion period, inhibition of autophagy with berberine [3] or curcumin [4] significantly mitigates I/R injury, which reduces the scope of MI and improves cardiac function. These findings suggest that excessive autophagy plays an adverse role during I/R period injury.…”
Section: Introductionmentioning
confidence: 99%